Associations of estimated plasma volume status with 30-day mortality and 1-year mortality in patients with intracerebral hemorrhage: a study of the MIMIC-IV database and the hospital information system - Shen, Yongze; Shen, Yingjie; Wang, Yaolou; Hu, Renjie; Xu, Hangjia; Feng, Yuyang; Yang, Yang; Zhang, Xiangtong; Liang, Hongsheng (Frontiers in Neurology, 2025)
AimThis study aims to investigated the associations between estimated plasma volume status (ePVS) and 30-day and 1-year mortality in intracerebral hemorrhage (ICH) patients, providing insights into the management in ICH.MethodsData of adult ICH patients were extracted from both the Medical Information Mart for Intensive Care IV (MIMIC-IV) database and the Hospital Information System (HIS) in this retrospective cohort study. Univariate and multivariate Cox regression analyses, and restricted cubic spline plots (RCS) were conducted to explore the associations between ePVS levels and both 30-day and 1-year mortality, with hazard ratios (HR) and 95% confidence intervals (CI) used for evaluation. Subgroup analyses were performed to further investigate these associations.ResultsAmong 2,512 eligible patients from the MIMIC-IV database, 655 (26.07%) died within 30 days, with 1,254 (49.92%) had died by the 1-year follow-up. After adjusting for covariates, elevated ePVS was independently associated with both 30-day mortality (HR = 1.05, 95%CI: 1.01–1.09) and 1-year mortality (HR = 1.09, 95% CI: 1.06–1.13). Compared to patients with ePVS levels of [4.63–5.79), those with ePVS levels ≥5.79 had a higher risk of 30-day mortality (HR: 1.36, 95%CI: 1.12–1.64) and 1-year mortality (HR = 1.24, 95% CI: 1.08–1.42). Among 515 eligible patients from the HIS, 132 (25.60%) died within 30 days, with 288 (55.90%) mortality observed at 1-year follow-up. After adjusting for covariates, elevated ePVS was independently associated with both 30-day mortality (HR = 1.33, 95%CI: 1.23–1.43) and 1-year mortality (HR = 1.26, 95% CI: 1.18–1.35). Comparing to patients with ePVS levels of [4.63–5.79), those with ePVS levels of ≥5.79 had a higher risk of 30-day mortality (HR:2.21, 95%CI: 1.48–3.30) and 1-year mortality (HR = 2.75, 95% CI: 2.04–3.72). Additionally, subgroup analyses demonstrated that ePVS was significantly associated with 30-day mortality or 1-year mortality derived from MIMIC-IV and HIS in most subgroups (p < 0.05). And RCS analysis indicates that, whether using MIMIC-IV or HIS data, ePVS was linearly associated with 30-day or 1-year mortality.ConclusionHigher ePVS levels may be a potential risk factor for 30-day and 1-year mortality in ICH patients, suggesting that timely monitoring and stabilization of ePVS could improve prognosis in this population. However, further studies are needed to validate these fingings.